IL25 Enhanced Colitis-Associated Tumorigenesis in Mice by Upregulating Transcription Factor GLI1 - Liu, Junxi; Qian, Bingxiu; Zhou, Lin; Shen, Gang; Tan, Yandan; Liu, Siqi; Zhao, Zewei; Shi, Jianglin; Qi, Weiwei; Zhou, Ti; Yang, Xia; Gao, Guoquan; et al. (Frontiers in Immunology, 2022)
Interleukin-25 (IL17E/IL25) plays an important role in colitis and intestinal homeostasis. However, the expression and biological role of IL25 in colorectal cancer is poorly understood. In this study, we show that IL25 is mainly expressed by cancer stem cells in the colorectal cancer microenvironment. Genetic deletion of IL25 inhibited tumor formation and growth and prolonged survival in AOM/DSS treated mice. IL25 stimulated cancer organoid and cancer cells sphere formation and prevented tumor from chemotherapy-induced apoptosis. Mechanistically, IL25 upregulated stem cell genes LGR5, CD133 and ABC transporters via activating Hedgehog signaling pathway. IL25 inhibited phosphorylation of AMPK and promoted GLI1 accumulation to maintain cancer stem cells. Moreover, IL25 expression was associated with poor survival in patients with metastatic colorectal cancer. Taken together, our work reveals an immune-associated mechanism that extrinsically confers cancer cell stemness properties. Our results first demonstrated that IL25, as a new powerful endogenous Hedgehog pathway agonist, could be an important prognostic factor and therapeutic target for CRC.